Research Progresses in Immunological Checkpoint Inhibitors for Breast Cancer Immunotherapy - Zhang, Wenxiang; Kong, Xiangyi; Ai, Bolun; Wang, Zhongzhao; Wang, Xiangyu; Wang, Nianchang; Zheng, Shan; Fang, Yi; Wang, Jing (Frontiers in Oncology, 2021)
Tumor immune escape refers to the phenomenon in which tumor cells escape the recognition and attack of the body’s immune system through various mechanisms so that they can survive and proliferate in vivo. The imbalance of immune checkpoint protein expression is the primary mechanism for breast cancer to achieve immune escape. Cytotoxic T lymphocyte antigen 4 (CTLA4) and programmed cell death protein 1 (PD-1)/programmed cell death protein-ligand 1 (PD-L1) are critical immune checkpoints for breast cancer. Immune checkpoint inhibitors block the checkpoint and relieve its inhibition effect on immune cells, reactivate T-cells and destroy cancer cells and restore the body’s ability to resist tumors. At present, immunological checkpoint inhibitors have made significant progress in breast cancer immunotherapy, and it is expected to become a new treatment for breast cancer.